Prevalence and Associated Factors with Respiratory Problems among Industrial Workers - Pradhan, M; Silwal, M (Journal of Gandaki Medical College-Nepal, 2018)
Background: In food processing industry, hazardous contaminants are generated. Flour dust has been introduced as one of the effective factors in the prevalence of respiratory disorders among the workers of the flour production factories. Objectives: To assess the prevalence and associated factors with respiratory problems among industrial workers. Methods: A cross-sectional descriptive study was used for the study. Non- probability purposive sampling technique was applied to choose flour industry and consecutive sampling technique was applied to select the sample from the industry. Hundred fifty respondents were taken as sample and self-administered structured interview questionnaire was used to collect the data. Results: The study revealed that more than half 103 (68.70%) of the respondents had work-related respiratory problems. The prevalence of cough, phlegm, breathlessness, chest tightness and whistling problems were 100 (66.67%), 58 (38.67%), 65 (43.33%), 9 (6.0%) and 4 (2.67%). Among different demographic variables, association of respiratory problems was found with religion (p value = 0.015), income per months of respondents (p value = 0.034) and the information they had about work-related respiratory problems (p value = 0.000). Conclusions: The study shows that there is higher prevalence of respiratory problems among industrial workers. Also, it shows there is association of respiratory problem with exacerbating factors and health checkup facility in the industry. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 46-51